Hybrid but One sided : Women and Hybrid Peace Orders in Dagbon, Northern Ghana - Dade, Felix (2023)
This research explores socio-cultural beliefs and practices that influenced women’s engagement in the 2002-2019 chieftaincy conflict resolution affairs in Dagbon. Inspired by hybrid peace governance, gender essentialism and social constructionism, cultural practices that influence Dagbon women’s engagement in peace spaces are analysed based on interview data. The research enters contestations in the critical peace field in two ways. Firstly, it contests feminist scholars’ homogenous view of women and peace by presenting context-specific push and pull factors for women’s engagement in the hybrid peace process. Secondly, it observes peace orientations – liberal, traditional and hybrid – by their structure and encounters with local culture restrict women’s engagement. The research generates insights into women’s engagement in a tripartite collaboration between the Ghanaian State, the chieftaincy institution and third-sector actors navigating the liberal-local peace values to address a chieftaincy conflict through three research questions: (a) how do women in Dagbon participate in hybrid peace orders in the chieftaincy conflict resolution affairs in practice? (b) how is women’s participation in the Dagbon chieftaincy conflict resolution affairs promoted by their socio-cultural beliefs, traditions and practices? (c) how is women’s participation in the Dagbon chieftaincy conflict resolution affairs restricted by their socio-cultural beliefs, traditions and practices? Thirteen separate interviews and a group interview from fieldwork were analysed manually with Microsoft Word and ATLAS.ti software. Findings revealed women engaged informally in the hybrid order in seven ways, includ-ing reducing tensions, peace education, appearing as witnesses, providing cultural advice, mediating community conflict, secret-channeling vital information to stakeholders, and mobilizing and building women’s capacity. Three cultural aspects of the Dagbon society, thus, women chiefs’ system, reverence for old women and women in the royal courtyard, and women’s performance of social roles, bring them into informal spaces of peace. How-ever, structural male dominance, beliefs and practices of Islam and African traditional religion, and women’s use of gendered language during the conflict combine to restrict women’s participation in the formal peace spaces. The research recommends more gender-focused studies into the push-and-pull factors of women’s engagement in liberal-local orders. Also, gender mainstreaming homegrown hybrid orders for other non-state conflicts in Ghana is recommended.